Comparison of Approaches to Photometric Redshift Estimation of Quasars. Issue Volume 11:Issue S319(2015) (17th August 2016) - Tu, Yang; Zhang, Yan-Xia; Zhao, Yong-Heng; Tian, Hai-Jun
Abstract: We probe many kinds of approaches used for photometric redshift estimation of quasars, including KNN (K-nearest neighbor algorithm), Lasso (Least Absolute Shrinkage and Selection Operator), PLS (Partial Least Square regression), ridge regression, SGD (Stochastic Gradient Descent) and Extra-Trees.